RESILIENSI PEREMPUAN KEPALA KELUARGA PASCA KARHUTLA (RESILIENT OF FEMALE-HEADED HOUSEHOLDS AFTER FOREST AND LAND FIRES) - ELIA DAMAYANTI (Jurnal Ilmu Politik dan Studi Sosial Terapan, 2025)
The study focuses on the resilience of female-headed households after forest and land fires. The research aims to understand the impact of forest and land fires on the livelihoods of these households and their resilience to climate change. The study uses a systematic literature review (SLR) method to gather and analyze data from various studies. The research aims to identify relevant articles, their relevance to the study, and the relevance of the study to the field. The study includes two types of studies: one on the role of women in community resilience to climate change, another on the intersectional lens of gender and ethnicity. The study aims to provide a nuanced assessment of livelihood resilience through the intersectional lens of gender and ethnicity, as well as a gendered lens for building climate resilience. The findings will be useful for policymakers, researchers, and policymakers in addressing the challenges faced by female-headed households in the face of climate change expecialy forest land fires.